Prediction of the reverberation time in rectangular rooms with non-uniformly distributed sound absorption - Neubauer, R.; Kostek, B. (Archives of Acoustics, 2001)
The aim of this paper is first to review the best known reverberation time formulae and then to show that the reverberation time cannot be thereby predicted accurately in cases mostly encountered in practice, where the sound field is not diffuse. Introducing a correction to Fitzroy’s formula allows better prediction of the reverberation time in the case of non-uniformly distributed sound absorption. Comparison of calculation results obtained on both the basis of classical equations and the new time reverberation formula introduced is shown. In addition, the results obtained by measuring reverberation conditions in situ and those predicted for the same enclosure are compared and conclusions drawn.